2014
DOI: 10.1159/000363699
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of the Antimicrobial Peptide LL-37 in the Protection of Neutrophil Extracellular Traps against Degradation by Bacterial Nucleases

Abstract: Neutrophil extracellular traps (NETs) have been described as a fundamental innate immune defence mechanism. They consist of a nuclear DNA backbone associated with different antimicrobial peptides (AMPs) which are able to engulf and kill pathogens. The AMP LL-37, a member of the cathelicidin family, is highly present in NETs. However, the function of LL-37 within NETs is still unknown because it loses its antimicrobial activity when bound to DNA in the NETs. Using immunofluorescence microscopy, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
116
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 31 publications
3
116
0
2
Order By: Relevance
“…We found that purified neutrophil DNA and NETs released by PMA-treated neutrophils, when supplemented with LL-37, were resistant to degradation by S. aureus, S. pneumoniae, and GAS nucleases (21). These results were recapitulated using other cationic AMPs, with the cationicity of the agents correlating with the degree of resistance to degradation.…”
Section: Degradation Of Netsmentioning
confidence: 76%
See 2 more Smart Citations
“…We found that purified neutrophil DNA and NETs released by PMA-treated neutrophils, when supplemented with LL-37, were resistant to degradation by S. aureus, S. pneumoniae, and GAS nucleases (21). These results were recapitulated using other cationic AMPs, with the cationicity of the agents correlating with the degree of resistance to degradation.…”
Section: Degradation Of Netsmentioning
confidence: 76%
“…The relevance of NET evasion by pathogens is further supported by evidence that the body also appears to "fight back"-for example, high concentrations of the antimicrobial peptide, LL-37, within NETs increases resistance to the action of DNases (21), and the presence of anti-ACT in the sera of patients infected with B. pertussis indicates the participation of humoral responses in combating the specific pathways by which pathogens modify NETs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Strikingly, S aureus also has a strong ability to evade killing by NETs through release of both a nuclease and adenosine synthase . LL‐37 blocks nuclease activity, thus protecting it from degradation by the nuclease, and LL‐37‐treated NETs are distinctly more resistant to S aureus nuclease degradation than nontreated NETs . Respiratory viral infections are often implicated in CRS exacerbation .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bactericidal activity of extracellular DNA against Pseudomonas aeruginosa , a common respiratory pathogen in CF, was described [18]. Antimicrobial proteins bound to neutrophil extracellular traps may have several roles, including antimicrobial activity, and they also protect these structures against degradation induced by bacterial nucleases [19]. It is exciting to see that novel roles for extracellular DNA in the airways continue to be unraveled.…”
mentioning
confidence: 99%